Rod and Cone Connections With Bipolar Cells in the Rabbit Retina - Whitaker, Christopher M.; Nobles, Gina; Ishibashi, Munenori; Massey, Stephen C. (Frontiers in Cellular Neuroscience, 2021)
Abstract Rod and cone pathways are segregated in the first stages of the retina: cones synapse with both ON- and OFF-cone bipolar cells while rods contact only rod bipolar cells. However, there is an exception to this specific wiring in that rods also contact certain OFF cone bipolar cells, providing a tertiary rod pathway. Recently, it has been proposed that there is even more crossover between rod and cone pathways. Physiological recordings suggested that rod bipolar cells receive input from cones, and ON cone bipolar cells can receive input from rods, in addition to the established pathways (Pang et al., 2010). To image their rod and cone contacts, we have dye-filled individual rod bipolar cells in the rabbit retina. We report that approximately half the rod bipolar cells receive one or two cone contacts. Dye-filling AII amacrine cells, combined with subtractive labeling, revealed most of the ON cone bipolar cells to which they were coupled, including the occasional blue cone bipolar cell, identified by its contacts with blue cones. Imaging the AII-coupled ON cone bipolar dendrites in this way showed that they contact cones exclusively. We conclude that there is some limited cone input to rod bipolar cells, but we could find no evidence for rod contacts with ON cone bipolar cells. The tertiary rod OFF pathway operates via direct contacts between rods and OFF cone bipolar cells. In contrast, our results do not support the presence of a tertiary rod ON pathway.